2018
DOI: 10.1259/dmfr.20180052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and imaging characteristics of nasopharyngeal and eustachian tube tonsilloliths in 2244 patients determined using computed tomography

Abstract: The prevalence of NT and ET on CT was lower than that of palatine and lingual tonsilloliths. However, since they are encountered more frequently than clinically significant calcifying diseases such as retropharyngeal calcific tendinitis, clinicians should be able to correctly diagnose NT and ET based on their anatomical features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The palatine tonsils are in the foreground in Waldeyer's lymphatic ring and can become calcified. The lingual and nasopharyngeal tonsils follow palatine tonsils 32,33 . We observed nasopharyngeal tonsillar calcifications in PR and CBCT (Figure 3).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The palatine tonsils are in the foreground in Waldeyer's lymphatic ring and can become calcified. The lingual and nasopharyngeal tonsils follow palatine tonsils 32,33 . We observed nasopharyngeal tonsillar calcifications in PR and CBCT (Figure 3).…”
Section: Discussionmentioning
confidence: 76%
“…The lingual and nasopharyngeal tonsils follow palatine tonsils. 32,33 We observed nasopharyngeal tonsillar calcifications in PR and CBCT (Figure 3).…”
Section: Discussionmentioning
confidence: 92%
“…Calcifications in maxillofacial region such as tonsilloliths may be incidental findings in X-ray panoramic radiographs in daily practice, whenever there is an indi-cation [18]. Previous studies reported that the detection of palatine tonsilloliths varies, and the prevalence in CT is 16.0-46.6% and in panoramic radiographs -7.3-13.4% only [7]. Two-dimensional image, superimposition of structures, distortion, and magnification may be diagnostic challenges in interpretation of panoramic radiographs [2,9,13,19].…”
Section: Discussionmentioning
confidence: 99%
“…They may be asymptomatic or cause dysphagia, globus sensation, halitosis, otalgia, peritonsil-lar abscess, swelling in the tonsillar fossa, glossopharyngeal neuralgia, orofacial pain, upper airway obstruction, and sleep breathing disorders. They may be incidentally found in three-and two-dimensional radiological examinations [1][2][3][4][5][6][7][8][9][10][11][12][13]. TLs appear as small opacities, overlapping the middle portion of mandible ramus, or as multiple poorly defined radio-opacities, which may be oval, round, or irregular in shape, superimposed on the soft tissues' shadows.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical diagnoses of CT of the rotator cuff were made based on the classic symptoms and radiographical evidence, and were nally con rmed by pathological diagnoses after the operation. The American Shoulder and Elbow Surgeons (ASES) scores [11], University of California at Los Angeles (UCLA) scores [2], and VAS scores were assessed preoperatively. All scores were reported by the patients themselves.…”
Section: Methodsmentioning
confidence: 99%